'Cruel to be kind?' Professionalization, politics and the image of the abstinent psychoanalyst, c. 1940–80. (April 2017) - Koch, Ulrich
This article investigates the changing justifications of one of the hallmarks of orthodox psychoanalytic practice, the neutral and abstinent stance of the psychoanalyst, during the middle decades of the 20th century. To call attention to the shifting rationales behind a supposedly cold, detached style of treatment still today associated with psychoanalysis, explanations of the clinical utility of neutrality and abstinence by 'classical' psychoanalysts in the United States are contrasted with how intellectuals and cultural critics understood the significance of psychoanalytic abstinence. As early as the 1930s, members of the Frankfurt School discussed the cultural and social implications of psychoanalytic practices. Only in the 1960s and 1970s, however, did psychoanalytic abstinence become a topic within broader intellectual debates about American social character and the burgeoning 'therapy culture' in the USA. The shift from professional and epistemological concerns to cultural and political ones is indicative of the changing appreciation of psychoanalysis as a clinical discipline: for psychoanalysts as well as cultural critics, I argue, changing social mores and the professional decline of psychoanalysis infused the image of the abstinent psychoanalyst with nostalgic longing, making it a symbol of resistance against a culture seen to be in decline.